Elements of nurses’ professional imagein electronic media and their contexts. The opinion of professionally active nurses - Sykut, Anna; Massalska, Klaudia; Dobrowolska, Beata (Nursing in the 21st Century, 2016)
ELEMENTS OF NURSES’ PROFESSIONAL IMAGE IN ELECTRONIC MEDIA AND THEIR CONTEXTS. THE OPINION OF PROFESSIONALLY ACTIVE NURSESAim. The aim of the research was to determine the elements of a nurses’ professional image, which most frequently appear in the media and the analysis of their connotations.Material and method. A survey was conducted on 171 women and 10 men; professionally active nurses. The study was carried out in 2015 using a questionnaire created by the author .Results. Among the most common elements influencing the nurses’ professional image in electronic media there were strikes/ protests (54.1%) and the nurses’ external appearance (40.9%). The tone of the above mentioned elements was assessed by the respondents as indifferent. According to the surveyed nurses, the most infrequently appearing professional traits were: confidence (7.7%), independence (10.5%), honesty and conscientiousness (13.3%). The overtone of these elements was evaluated as indifferent except for the ‘independence’ which was described by 36.5% of the respondents as negative. According to the respondents, the efforts to improve the image in electronic media should be done by professional organizations of nurses and midwifes and the nurses themselves. The most important task that should be undertaken by professional organizations in order to improve the overall image would be to increase wages and improve nurses’ working conditions and their identification with the professional environment.Conclusions. The most frequently appearing elements of the professional image of nurses in the electronic media were strikes and protests. Rarely such features of nurses and the profession as self-confidence, independence and honesty and conscientiousness were mentioned. Thus there is a great need for acting towards changing the nurses’ professional image in the electronic media.